(untitled) (Razi Medical Journal, 2025)
Hand hygiene is the most essential action to prevent the cross-transmission of harmful microorganisms in health care facilities and to decrease the prevalence of Healthcare-Associated Infections, the lack of related knowledge among medical students could cause adverse consequences as they constitute the future health workforce. The aim of this study is to assess the level of knowledge regarding hand hygiene among preclinical students, clinical students, and intern doctors at Misurata University. A cross sectional study was done on 255 participants from all study years in the faculty of medicine at Misurata University in July 2025, using an online questionnaire based on a validated WHO 25-points survey and data were analyzed on SPSS-25. We found that the overall mean knowledge score about hand hygiene (HH) among medical students and interns was moderate. A significant difference was observed between preclinical and clinical years students, the latest had higher knowledge scores. No significant difference in knowledge scores between male and female participants. Participants who received formal training in hand hygiene in the last three years had significantly higher knowledge scores compared to those who did not. This study reveals that there were significant gaps between preclinical & clinical students regarding knowledge of hand hygiene. The overall score was moderate, so regular training sessions and the need to enhance teaching methods are recommended to achieve better results in the future.